A Hybrid Method for Multi-Criteria Group Decision Making under Pythagorean Fuzzy Environment. (3rd September 2021) - Singh, Yograj; Bisht, Dinesh C. S.
ABSTRACT: Fuzzy set theory has an important role in the evolution of multicriteria decision-making methods. Different kinds of fuzzy sets are used to handle different kind of uncertain situations. In this work, we have proposed a hybrid method to overcome the shortcomings of ELimination Et Choice Translating Reality 1 (ELECTRE 1), decision-making method by incorporating steps borrowed from VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) method in Pythagorean fuzzy environment. ELECTRE 1 is easy to use and simple in calculations, but it is an outranking method, thereby it is not capable to rank all the alternatives. This method only provides ranking of few alternatives while ignoring the ranking of rest of the considered alternatives. In real-life scenario, sometimes ranking of all the considered alternatives may be required to make appropriate decisions. Therefore, to serve this facility in ELECTRE 1, we have proposed a hybrid method that combines the steps from ELECTRE 1 and VIKOR methods in Pythagorean fuzzy environment. Additionally, the proposed method considers a group of decision makers while calculating weights of different criteria accordingly. The proposed method is also implemented on a real-world problem.